2006
DOI: 10.1111/j.1365-2133.2006.07147.x
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitination of molluscum body and its implications for pathophysiology

Abstract: References1 Gupta AK, Ryder JE, Nicol K, Cooper EA. Superficial fungal infections: an update on pityriasis versicolor, seborrheic dermatitis, tinea capitis, and onychomycosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
(17 reference statements)
0
9
0
Order By: Relevance
“…Recently, we have reported that ubiquitination is involved in the elimination of molluscum bodies 1 . We found increased expression of ubiquitin in the molluscum bodies from several healthy infants.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…Recently, we have reported that ubiquitination is involved in the elimination of molluscum bodies 1 . We found increased expression of ubiquitin in the molluscum bodies from several healthy infants.…”
mentioning
confidence: 59%
“…In our recent study, ubiquitination was strongly expressed within the skin lesions of molluscum contatigiosum in healthy infants 1 . We describe a case of agminated mollusca contagiosa with attenuated ubiquitination of molluscum bodies, with underlying malignant lymphoma.…”
mentioning
confidence: 70%
“…74 Extensive lesions can occur in immunocompromised patients, particularly those with AIDS. 86 Apoptosis is not increased in active lesions. 85 An additional mechanism appears to be involved in regression.…”
Section: Cowpoxmentioning
confidence: 97%
“…73 Antibodies to the virus have been found in nearly 60% of patients with skin lesions, suggesting a role for humoral immunity, but antibodies are less frequent in patients with AIDS. 86 This involves the ubiquitin-proteasome system (UPS). [75][76][77][78][79][80][81][82][83][84] Disseminated lesions can occur in HTLV-1 infection as well.…”
Section: Cowpoxmentioning
confidence: 99%
“…2 a-c). Next, immunofluorescence using anti-cleaved caspase 3 (Asp175) rabbit polyclonal antibody (Cell Signaling Technology, Beverly, MA, USA) was performed on deparaffinized lesional skin sections (5,6). Keratinocytes with shrunken nuclei showed cleaved caspase 3 in both the cytoplasm and the nucleus (Fig.…”
Section: Case Reportmentioning
confidence: 99%